Uji Beberapa Konsentrasi Ekstrak Tepung Daun Babadotan (Ageratum conyzoides L.) Dalam Mengendalikan Kepik Hijau (Nezara viridula L.)Pada Kacang Panjang(Vigna sinensis L.) - Kartika, Nurul Ika; Salbiah, Desita; Sutikno, Agus (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Green stink bugNezara viridula L. (Hemiptera: Pentatomidae) is one of the important pest on long beans plant.One alternative that can be used to minimize the application of chemical pesticides is an extract powder from the babadotan leaf (Ageratum conyzoides L.). This research is purpose  to get the better concentration of a babadotan’s leaf powder extract (Ageratum conyzoides L.) for controllinggreen stink bug Nezara viridula L. at long beans plant. This research was conducted at the Center for Agricultural Development and Plant Pests Laboratory Faculty of Agriculture, University of Riau from April to June 2015. This research was carried out experimentally by using completely randomized design (CRD) with 5 treatments and 4 replications.Treatment consists of several concentrations of  babadotan’s leaf powder extract 75 g/l of water, the concentration of 85 g/l of water, the concentration of 90 g/l of water, the concentration of 95 g/l of water, the concentration of 100 g/l of water. The parameters observed were the initial time of death (hours), lethal time 50 (hours), daily mortality (%),total mortality (%), lethal concentration 50 and 95 (LC50 and LC95) (%), temperature and humidity as supporting observations. The results showed that the concentration of  100 g/l of water caused total mortality 72,50%, this has not yet reached a good concentration in the control of green stink bug because not being able to control the green stink bug over 80%, while the value of LC95 obtained is greater than 10%, it is16,8% or equivalent to 168 g/l of water.   Keyword:Long bean (Vigna sinensis L.), Babadotan (Ageratum conyzoides L.), Green stink bug(Nezara viridula L.).